Hadiths Related With Mahdism As Manipulation Tool in Political Events of Early Period - Kazimov, Shaino (Scholarya Demo Journal of Ruby, 2021)
This research focuses on Mahdism and how it is used as manipulation tool in politics by some Muslim denominations. Following the advent of Islam, the newly established Islamic government rapidly expanded its territories through massive conquests. Along with the advantages of conquest, the Islamic administration experienced the disadvantages of expansion over time. The issue of Mahdism could be one of these negative developments. Following the Prophet's death, the Muslim public was subjected to widespread incitement, with thousands of Muslims killing each other in civil wars. Endless civil wars exhausted the Muslims, so they wanted the civil war to end as soon as possible. This idea, desires, and wishes drew them into the Islamic World's widespread expectation of a savior Masih and Mahdi, which was influenced by external sources. However, the concept of Mahdism soon became an important factor in the political goals of some aristocratic elites, and a variety of interpretations of Mahdism emerged. Previously, Hashimids created such narratives. Following that, the Umayyads used the same strategy against them. When the Abbasids came to power, they used Mahdist narration to maintain their rule. Mahdist ideas led to different interpretations of religious scripts, resulting in schism and the emergence of various sects in the Islamic World. The feelings of fragmentation grew stronger due to this new ideology. Consequently, almost every sect has created its own Mahdi character. Various sects appeared, each with their own interpretation and approach to Mahdism. Over the time, these narrations surrounding the problem of the Mahdi, gained foothold in hadith (tradition) literature, and had become inseparable part of theological issues for some sects.